Enhancing EFL Learners’ Quality of Interaction through Ground Rules Incorporated in Collaborative Strategic Reading - Fatemeh Khonamri; Marjan Sangari; Baqer Yaqubi (Universitas Pendidikan Mandalika, 2021)
The present research tries to investigate the impact of teaching Ground Rules (GRs) on EFL learners’ quality of interaction while they are implementing Collaborative Strategic Reading (CSR). To this purpose, five Iranian EFL intermediate learners who were learning English language in an institute in Iran were selected. In this study, after three sessions of implementing CSR, 5 GRs were explicitly taught to the learners, and learners’ interaction was analyzed for three subsequent sessions to investigate whether teaching GRs has influenced learners’ quality of interaction during the implementation of CSR. The study was done on the platform of adobe-connect. The researcher recorded learners’ interactions during six sessions for further analysis. Qualitative research design was applied in this study to examine the changes in the quality of learners’ interaction. The result of the study indicated that teaching GRs promoted the quality of learners’ interaction during the implementation of CSR.